Erratum: SO, J.H. & Lee, N.S. (2017) The Origin of New Natural hybrid, Goodyera × maximo-velutina (Orchidaceae) from Jeju Island, Korea. Phytotaxa 317 (1): 61–68. - So, Ji-Hyeon; Lee, Nam-Sook (Phytotaxa, 2017)
N/A